Gestión administrativa y financiera y su incidencia en la calidad de servicio de la telefonía y televisión satelital de la corporación nacional de telecomunicaciones Cnt, cantón La Maná, año 2013 - Carrera Bastidas, Maryuri Rossmery (2015)
The current draft thesis was developed at the National Telecommunications Corporation (CNT), located in Canton La Mana, belonging to the province of Cotopaxi; the range of services offered by the National Telecommunications Corporation CNT in finding innovative solutions for their users, but in this canton quality of service of this institution in relation to the area of cellular and satellite television is in poor reception. With the main objective to assess the administrative and financial management and its impact on quality of service of mobile telephony and satellite television, the National Telecommunications Corporation (CNT) La Mana, 2013-2014; through the application of research techniques such as surveys, direct observation and the SWOT analysis, whose evolution allowed to appreciate that there are shortcomings in staff since there is not an organization, nor manual defined functions, causing chaos in the performance of daily and harming the quality of service offered to the lamanense citizenship through surveys of users and workers of this institution was to determine the incidence of administrative and financial management in the quality of service where the results show that there nonconformity of work users and poor administrative and financial management in this institution; affirmatively demonstrating the general hypothesis at the beginning. For the above reasons it is recommended to encourage is put into practice the strategies to improve the quality of service of mobile telephony and satellite television.